Fe-induced crystallization and microstructural evolution of germanium thin films on glass substrates - Kulakci, Mustafa; Kabacelik, Ismail (World Scientific Publ Co Pte Ltd, 2026)
This study investigates the iron (Fe)-induced crystallization behavior, structural evolution, and electrical properties of amorphous germanium (alpha-Ge) thin films deposited on Corning glass substrates. A thin Fe interlayer was introduced to catalyze metal-induced crystallization (MIC)and the subsequent metal-induced layer exchange (MILE) during post-annealing at temperatures between 300 and 500 degrees C. Raman spectroscopy and X-ray diffraction (XRD) analyses reveal a progressive transformation from amorphous to polycrystalline Ge (poly-Ge), accompanied by the development of a dominant (111) orientation. Fe-assisted crystallization significantly reduces the crystallization temperature compared with conventional solid-phase processes, enabling pronounced grain coalescence and strain relaxation even at 500 degrees C. Raman-derived parameters indicate a decrease in lattice strain and an increase in crystallite size. Concurrently, William-son-Hall(W-H) analysis confirms reductions in dislocation density and internal stress with higher annealing temperatures. Together, the Raman and XRD results demonstrate that Fe effectively promotes atomic rearrangement and stress relaxation throughout crystallization. Electrical measurements further demonstrate that Fe enhances the conductivity of Ge films by more than a factor of two, resulting in ohmic current-voltage (I-V) characteristics with improved carrier transport. These findings demonstrate that Fe is an efficient catalyst for low-temperature Ge crystallization, enabling the formation of uniform, low-defect poly-Ge films that may be promising for applications in thin- film transistors and next-generation photovoltaic devices; however, further electrical characterization is needed to validate their performance
Keywords: Fe-Induced Crystallization; Ge Thin Films; Glass Substrate; Grain Growth